2022
DOI: 10.3389/fmicb.2022.907961
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, Divergence Time Estimation and Biogeography of the Genus Onnia (Basidiomycota, Hymenochaetaceae)

Abstract: Species of Onnia are important tree pathogens and play a crucial role in forest ecosystems. The species diversity and distribution of Onnia have been studied, however, its evolutionary history is poorly understood. In this study, we reconstructed the phylogeny of Onnia using internal transcribed spacers (ITS) and large subunit (LSU) rDNA sequence data. Molecular clock analyses developed the divergence times of Onnia based on a dataset (ITS + LSU rDNA + rpb1 + rpb2 + tef1α). Reconstruct Ancestral State in Phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 76 publications
2
12
0
Order By: Relevance
“…Macrofungi have been widely applied for biogeographical analyses [ 24 , 48 , 49 , 50 , 51 ]. Our study suggested that the species distribution and speciation of Pseudoplagiostomataceae had a particular biogeographical pattern, and these species appeared to originate in Asia, particularly in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrofungi have been widely applied for biogeographical analyses [ 24 , 48 , 49 , 50 , 51 ]. Our study suggested that the species distribution and speciation of Pseudoplagiostomataceae had a particular biogeographical pattern, and these species appeared to originate in Asia, particularly in Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from fungal mycelia grown on PDA, using a kit (OGPLF-400, GeneOnBio Corporation, Changchun, China) according to the manufacturer’s protocol [ 24 ]. Gene sequences were obtained from five loci including the internal transcribed spacer regions with the intervening 5.8S nrRNA gene (ITS), the partial large subunit nrRNA gene (LSU), the partial DNA-directed RNA polymerase II subunit two gene ( rpb2 ), the partial translation elongation factor 1-alpha gene ( tef1α ), and the partial beta-tubulin gene ( tub2 ) were amplified by the primer pairs and polymerase chain reaction (PCR) programs listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The internal transcribed spacers (ITS), large subunit of nuclear ribosomal RNA gene (LSU), and small subunit mitochondrial rRNA gene (mtSSU) were amplified with primer pairs ITS 5 (5′‐GGA AGT AAA AGT CGT AAC AAG G‐3′) and ITS 4 (5′‐TCC TCC GCT TAT TGATAT GC‐3′; White et al., 1990 ), LR0R (5′‐ACC CGC TGA ACT TAA GC‐3′) and LR7 (5′‐TAC TAC CAC CAA GAT CT‐3′; ), and MS1 (5′‐CAG CAG TCA AGA ATA TTA GTC AAT G‐3′) and MS2 5′‐GCG GAT TAT CGA ATT AAA TAA C‐3′; White et al., 1990 ), respectively. The PCR procedures were as follows: for ITS and mtSSU regions, an initial denaturation at 95°C for 3 min, followed by 34 cycles at 94°C for 40 s, 54°C for ITS and 55°C for mtSSU for 45 s and 72°C for 1 min, and a final extension of 72°C for 10 min; for the LSU region, an initial denaturation at 94°C for 1 min, followed by 34 cycles at 94°C for 30 s, 50°C for 1 min and 72°C for 1.5 min, and a final extension of 72°C for 10 min ( Zhou et al., 2021 ; Zhao et al., 2022c ). The PCR products were sequenced using BGI Tech Solutions (Beijing Liuhe Co., Ltd., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…biology.duke.edu/fungi/mycolab/primers.htm ), and MS1 (5′-CAG CAG TCA AGA ATA TTA GTC AAT G-3′) and MS2 5′-GCG GAT TAT CGA ATT AAA TAA C-3′; White et al, 1990), respectively. The PCR procedures were as follows: for ITS and mtSSU regions, an initial denaturation at 95°C for 3 min, followed by 34 cycles at 94°C for 40 s, 54°C for ITS and 55°C for mtSSU for 45 s and 72°C for 1 min, and a final extension of 72°C for 10 min; for the LSU region, an initial denaturation at 94°C for 1 min, followed by 34 cycles at 94°C for 30 s, 50°C for 1 min and 72°C for 1.5 min, and a final extension of 72°C for 10 min (Zhou et al, 2021;Zhao et al, 2022c). The PCR products were sequenced using BGI Tech Solutions (Beijing Liuhe Co., Ltd., Beijing, China).…”
Section: Dna Extraction Pcr and Sequencingmentioning
confidence: 99%
“…Onnia species are distributed primarily in the northern hemisphere and are known for parasitizing gymnosperms. Relatively recent work established six well-supported species of Onnia in Europe, Asia and North America (Ji et al, 2017), with a seventh added more recently (Zhao et al, 2022). Among these species, Onnia tomentosa and O. leporina had occurrence records in North America before the publication of the generic revision of Ji et al (2017) (Global Biodiversity Information Facility, 2023).…”
mentioning
confidence: 99%